Facile synthesis of 1-trifluoromethylalkenes via the decarboxylation of α-trifluoromethyl-β-lactones1. Issue 62 (11th August 2015) - Veeraraghavan Ramachandran, P.; Otoo, Barnabas
<x xml:space="preserve">Abstract</x> DCC-mediated cyclodehydration of α-trifluoromethyl-β-hydroxy acids provides α-trifluoromethylated β-lactone intermediates, without loss of stereoselectivity. These lactones undergo facile decarboxylation providing a simple route to obtain both alkyl and aryl 1-trifluoromethyl alkenes in excellent yields and stereoselectivity.